A developing novel alternative bio-oxidation approach to treat low-grade refractory sulfide ores at circumneutral pH - Hein, Guillermo; Mahandra, Harshit; Ghahreman, Ahmad (Frontiers in Sustainable Resource Management, 2023)
The extensive neutralization required in acidic bio-oxidation, a conventional pretreatment for low-grade refractory matrices in the gold industry, constitutes one of the principal drawbacks due to the large volume of waste streams. Performing an oxidative pretreatment at circumneutral pH with an in-situ neutralization would avoid the production of undesirable waste, causing potential economic and environmental advantages. For the first time, this investigation evaluates a novel process involving a biological oxidative pretreatment for low-grade refractory ore using two biosafety level 1 neutrophilic microorganisms encompassing Thiobacillus Thioparus and Starkeya Novella at near-neutral pH. Optimal bacterial growth conditions were determined regarding the culture medium and initial energy source using UV-visible and manual cell counting (cell/mL). Thereafter, biological oxidation of different matrices, including first elemental sulfur and subsequently a refractory sulfidic ore, was evaluated in batch flask cultures and then scaled up into a bioreactor using optimal experimental conditions. Results revealed that culture media containing ca. 4.5 g/L and ca. 0.9 g/L thiosulfate favored biological oxidation of the refractory sulfidic ore using Thiobacillus Thioparus and Starkeya Novella, respectively, which led to corresponding sulfide oxidation of 27% and 14% within 10 days, comparable to reported studies. The biological action was confirmed by C/S detector and SEM technique of pre- and post-pretreatment residues. Overall, this research is a step forward to advance the understanding of a biological pretreatment out of the highly acidic pH range, promoting the view of a net-zero target by potentially reducing the production of more significant waste streams compared to conventional operations.